نحو نظرية إقتصادية حديثة للنمو في ظل أزمة الكساد الإقتصادي العالمي - الحرتسي، حميد عبدالله (جامعة حسيبة بن بو علي بالشلف - مخبر العولمة واقتصاديات شمال إفريقيا, 2010)
This paper aims to describe essential characteristics which governe the moderne form of establishing an economic growth theory. \ We used the description which is one of deductive method instruments to find an answer to our problematic about obstacles hindering theoreticians to build an integrated theory in the actual contexte. \ Our findings indicates that economic growth theory frame still been ambiguous as a result of conflicted differences between classic and moderne growth theory, built on dogmas and a non agreed proposals.
Keywords: السياسة المالية -- النظريات الإقتصادية -- الاسواق المالية -- الرهن -- الكساد الإقتصادي